2012
DOI: 10.1007/s00125-012-2652-8
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle-specific overproduction of constitutively activated c-Jun N-terminal kinase (JNK) induces insulin resistance in mice

Abstract: Aims/hypothesis Although skeletal muscle insulin resistance has been associated with activation of c-Jun N-terminal kinase (JNK), whether increased JNK activity causes insulin resistance in this organ is not clear. In this study we examined the metabolic consequences of isolated JNK phosphorylation in muscle tissue. Methods Plasmids containing genes encoding a wild-type JNK1 (WT-JNK) or a JNK1/JNKK2 fusion protein (rendering JNK constitutively active; CA-Jnk) were electroporated into one tibialis anterior (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 38 publications
(45 reference statements)
5
49
0
1
Order By: Relevance
“…Ceramide has been reported to cause insulin resistance by impairing insulin signalling at the level of Akt (SchmitzPeiffer et al 1999, Bruce et al 2006, Holland et al 2007). In addition, ceramide is a potent activator of inflammatory molecules, including c-Jun N-terminal kinase (JNK; Westwick et al 1995) and nuclear factor kB/inducer of k kinase (IKK) (Wang et al 1999), which have been reported to be associated with the development of muscle insulin resistance (Itani et al 2002, Sriwijitkamol et al 2006, Henstridge et al 2012. However, while inflammation has been proposed as a critical factor causing insulin resistance, studies carried out by our group and other groups suggest that inflammation is not involved in the initiation of lipid-induced insulin resistance, but may be more important in the exacerbation and maintenance of insulin resistance once obesity is established .…”
Section: Lipid Intermediates Inflammation and Insulin Resistancementioning
confidence: 99%
“…Ceramide has been reported to cause insulin resistance by impairing insulin signalling at the level of Akt (SchmitzPeiffer et al 1999, Bruce et al 2006, Holland et al 2007). In addition, ceramide is a potent activator of inflammatory molecules, including c-Jun N-terminal kinase (JNK; Westwick et al 1995) and nuclear factor kB/inducer of k kinase (IKK) (Wang et al 1999), which have been reported to be associated with the development of muscle insulin resistance (Itani et al 2002, Sriwijitkamol et al 2006, Henstridge et al 2012. However, while inflammation has been proposed as a critical factor causing insulin resistance, studies carried out by our group and other groups suggest that inflammation is not involved in the initiation of lipid-induced insulin resistance, but may be more important in the exacerbation and maintenance of insulin resistance once obesity is established .…”
Section: Lipid Intermediates Inflammation and Insulin Resistancementioning
confidence: 99%
“…Lipid content was determined in the cardiac tissue using the methods previously described (Henstridge et al 2012;Matthews et al 2010;Weir et al 2013). Briefly, samples (20-30 mg wet weight) were homogenized in 100 μL PBS buffer, pH 7.47.…”
Section: Lipidomicsmentioning
confidence: 99%
“…Heart samples were lysed and protein concentration was determined and resolved by SDS-PAGE as previously described (Henstridge et al 2012). Immunoblotting was performed using the following primary antibodies: Hsp72 , H sp90 (Enz o Life Scien ces (fo rmerly Stressgen), PA, USA), and GAPDH (Cell Signaling, Danvers, USA).…”
Section: Western Blottingmentioning
confidence: 99%
“…This likely reflects a combination of the low level of expression of the receptors and intrinsic limitations of the approach 209 . Thus, we employed an alternate approach to address the physiological significance by characterizing the effect of overexpression of WT and canonical palmitoylation defective receptor constructs in mouse skeletal muscle 212,215 . Overexpression of the WT receptors for two weeks resulted in a constitutive increase in phosphorylation of AMPK, AKT and ERK.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the requirement for adiponectin receptor palmitoylation in a more physiological setting we employed in vivo electrotransfer (IVE) 212,215 to characterize the effects of overexpression of WT or canonical palmitoylation defective constructs, namely R1 C124A & R2 C135A…”
Section: Palmitoylation Of the Canonical Cysteine In R1 And R2 Is Reqmentioning
confidence: 99%